Peran Otoritas Pengawas dalam Menanggulangi Risiko dan Memperkuat Stabilitas Perbankan Syariah - Muzan, Amrul; Islami, Al Irhas; Putra, Aldy Noveriansyah; Kurnia, Febris Retno (TAWAZUN: Journal of Sharia Economic Law, 2024)
Islamic banking has experienced rapid growth as an alternative that aligns with Islamic principles, but it faces significant challenges in risk management and stability. This study examines the role of supervisory authorities in mitigating risks and enhancing the stability of Islamic banking. Using a qualitative approach through literature reviews and analysis of applicable regulations, this research identifies key challenges such as regulatory adaptation, risk management for Islamic financial products, and compliance with Islamic principles. Furthermore, the study proposes strategies for supervisory authorities, including regulatory innovation, international collaboration, and continuous education and training programs for industry players and supervisors. The findings reveal that the proactive role of supervisory authorities is crucial in maintaining the stability and sustainability of Islamic banking. Strategies such as risk-based supervision, the implementation of regulatory sandboxes, and enhanced synergy between supervisory authorities and Sharia Supervisory Boards (SSBs) are vital in addressing existing challenges. With effective supervision and the application of appropriate strategies, the stability of the Islamic financial system can be enhanced, supporting the sustainable growth of the Islamic economy.